PELESTARIAN KEARIFAN LOKAL MELALUI KEGIATAN EKSTRAKURIKULER DI SMP SWASTA AR-RAHMAN PERCUT - Yamin Dalimunthe, Ahmad; Hanum OK, Azizah (Jurnal Bilqolam Pendidikan Islam, 2024)
The purpose of this study was to analyze the implementation of extracurricular activities at SMP Ar-Rahman Percut as a means of preserving local wisdom. This study used a qualitative method with a case study approach to explore extracurricular activities at the school, especially in preserving local wisdom and its impact on students. The results showed that traditional dance extracurricular activities at SMP Ar-Rahman Percut are one of the effective media in preserving local wisdom. The traditional dances taught, such as Sekapur Sirih Dance, Surdu-Surdu Burangir Dance, and Mejuah-Juah Dance, have noble values ​​that include spiritual, moral, and social aspects. The implementation of this activity involves the transfer of values ​​from dance teachers to students through movement learning and explaining the philosophy behind the dance. Students who participate in this activity understand and internalize local wisdom values, such as togetherness, manners, and gratitude. In addition, they also show a love for local culture that is embedded in them, encouraging the spirit to continue preserving local wisdom in their environment. This study proves that traditional dance extracurricular activities not only develop students' artistic talents, but also shape character and strengthen cultural identity. Therefore, this activity can be a relevant learning model for other schools in an effort to preserve local cultural heritage. Full support from the school, teachers, and parents is the key to the success of implementing this program.